Boosting up crafts: rites and local production of pottery - Cvjetićanin, Tatjana (Rei Cretariae Romanae Fautorum Acta, 2022)
With the Roman rule in the province of Moesia Superior, a new form of incineration burials emerged, known as the Mala Kopašnica-Sase type. Pottery played an important role in these burials and was used in various phases of the ceremony, as well as grave goods. For the most part vessels were produced specifically for burial, as funerary pottery, withdrawn from use straight away and utilized in the canonized ritual, for food offerings and other rites. At present, the largest number of the known MKS type graves is excavated at Viminacium – capital of the province, Mt Kosmaj – imperial metalla and Mala Kopašnica – village. At all these sites pottery kilns were discovered as well. It seems that one of the consequences of the new burial rites was the development of a special branch of the local ceramic production. The growth in the pottery production was tightly connected with death.